(untitled) (Journal of Buffalo Science, 2024)
This study aimed to survey the prevalence of Fasciola spp. infection in cattle and buffaloes in Luang Prabang province, Lao PDR (Laos). To determine the prevalence of Fasciola spp. a total of 100 individual fecal samples (50 from buffaloes and 50 from cattle) were collected from smallholder farms in seven locations within Luang Prabang province. The samples were examined in the lab using the Benedek Sedimentation method and Mc Master egg counting techniques. The results showed an apparent prevalence of Fasciola spp. infection of 12% across all herds, with 5 native swamp buffaloes (5%) and 7 native cattle (7%) infected. When comparing three age groups, it was discovered that 25% (5/20) of all buffaloes infected with Fasciola spp. were 1-3 years old, accounting for 10% of all buffaloes. Among the cattle, 7 infected individuals were 1-3 years old, representing 14% of the 50 cattle sampled. Specifically, 20% (3/15) of cattle aged 1-3 years were infected, 14.29% (2/14) of less than a year old were infected, and 9.52% of cattle older than three years were infected. The results indicate that the highest mean infection rate occurred in animals aged 1 to 3 years (P < 0.05). A comparison between species revealed no significant effect of species on the prevalence of Fasciola spp. (P > 0.05). Farmers in the seven villages raised large ruminants on a free-range basis in paddy rice fields post-harvest and on natural fodder and pasture grass. Therefore, further research on the comparative prevalence of Fasciola spp. infection in cattle and buffaloes across different seasons and farm systems is recommended.